2009
DOI: 10.1002/ibd.20930
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-free solution derived from lactobacillus plantarum inhibits multiple NF-kappaB pathways and inhibits proteasome function

Abstract: Background-Bacteria play a role in inflammatory bowel disease and other forms of intestinal inflammation. Although much attention has focused on the search for a pathogen or inciting inflammatory bacteria, another possibility is a lack of beneficial bacteria that normally confer antiinflammatory properties in the gut. The purpose of this study was to determine whether normal commensal bacteria could inhibit inflammatory pathways important in intestinal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 49 publications
1
60
1
2
Order By: Relevance
“…Some probiotic strains maintain or restore the epithelial barrier function after pathogen challenge (Otte and Podolsky 2004) or proinflammatory cytokine stimulus (Resta-Lenert and Barrett 2006), and others alter the capacity of intestinal epithelial cells (IEC) to release proinflammatory mediators or directly modify immune cell activity. Studies using IEC cultures have shown the downregulation of the secretion of the proinflammatory chemokine IL-8 (Frick et al 2007; Kamada et al 2008;Ma et al 2004;O'Hara et al 2006) and other NF-jB regulated chemokines, such as MCP-1 (Petrof et al 2009) or CCL-20 (Sibartie et al 2009), as well as a mechanism for the inhibition of IP-10 secretion. Also, a number of works demonstrated that probiotic bacteria directly interacting with immune cells elicit a differential cytokine production, thereby driving the polarization of T cells toward T h 1, T h 2, T h 17 or regulatory T cells (Foligne et al 2007a, b;Kekkonen et al 2008;Latvala et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some probiotic strains maintain or restore the epithelial barrier function after pathogen challenge (Otte and Podolsky 2004) or proinflammatory cytokine stimulus (Resta-Lenert and Barrett 2006), and others alter the capacity of intestinal epithelial cells (IEC) to release proinflammatory mediators or directly modify immune cell activity. Studies using IEC cultures have shown the downregulation of the secretion of the proinflammatory chemokine IL-8 (Frick et al 2007; Kamada et al 2008;Ma et al 2004;O'Hara et al 2006) and other NF-jB regulated chemokines, such as MCP-1 (Petrof et al 2009) or CCL-20 (Sibartie et al 2009), as well as a mechanism for the inhibition of IP-10 secretion. Also, a number of works demonstrated that probiotic bacteria directly interacting with immune cells elicit a differential cytokine production, thereby driving the polarization of T cells toward T h 1, T h 2, T h 17 or regulatory T cells (Foligne et al 2007a, b;Kekkonen et al 2008;Latvala et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These results highlight a strain and stimulus-dependent protection by LB, which we suggest is enhanced for L. plantarum and L. salivarious against NmB by a factor secreted in their conditioned medium (Figure 2). In our study inflammatory attenuation by their conditioned medium was largely independent of TLR-2 (Figure 3), in contrast to others [40], so is unlikely to involve LB lipoteichoic acid, which can be shed in vesicles by some strains [41] and is highly anti-inflammatory [42,43].…”
Section: T L Bekele Et Almentioning
confidence: 47%
“…16,[30][31][32] Probiotic anaerobes have also been found to secrete anti-inflammatory agents. 25,33,34) Furthermore, our previous study showed that the flavonols quercetin, galangin, and fisetin enhance the production of NO suppressants by B. adolescentis. 25) However, whether these effects are distinct to flavonols and evoked by a characteristic structure of these compounds have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%